Alkaline metal fluoride synthesis as a subproduct of beta-spodumene leaching - Rosales, Gustavo Daniel (2013)
This paper investigated the development of new techniques to recover fluorine as three valuable fluorides: cryolithionite (Li3Na3Al2F12), sodium hexafluorosilicate (Na2SiF6) and cryolite (Na3AlF6). The synthesis of these compounds was carried out through three routes: I) by precipitation in situ during the leaching process of beta spodumene at different temperatures and different HF concentrations, to produce Li3Na3Al2F12; II) by precipitation adding NaOH to the leach liquor of beta spodumene, to produce Na2SiF6 and Na3AlF6; and III) by coprecipitation from pure reagents, to separately produce Li3Na3Al2F12, Na2SiF6 and Na3AlF6. Reagents and products were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), atomic absorption spectroscopy (AAS), scanning electronic microscopy (SEM) and electron probe microanalysis (EPMA). The experimental results indicate that the production of the fluorinated compounds was possible. Following route I), an enhancement of the crystal size was observed after increasing the concentrations of HF. It was also observed that a decrease in temperature favors precipitation of the solid. Furthermore, the presence of Na+ from albite (gangue) was essential for the formation of Li3Na3Al2F12. The compounds Na2SiF6 and Na3AlF6 were synthesized together using route II), with a recovery of 92%. Through route III) the three compounds were synthesized separately and these compounds were used as standards for XRD analysis.